2014
DOI: 10.1364/oe.22.023153
|View full text |Cite
|
Sign up to set email alerts
|

Finite-difference time-domain study of modulated and disordered coupled resonator optical waveguide rotation sensors

Abstract: We present a full-wave finite difference time domain (FDTD) study of a coupled resonator optical waveguide (CROW) rotation sensor consisting of 8 doubly degenerate ring resonators. First we demonstrate the formation of rotation-induced gap in the spectral pass-band of the CROW and show the existence of a dead-zone at low rotation rates which is mainly due to its finite size and partly because of the individual cavities losses. In order to overcome this deficiency, we modulate periodically the refractive indice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Recent development in photonic integrated circuit (PIC) technologies introduced various new types of sensors [4], including gyroscopes. Utilizing nano-/micro-optical devices such as photonic crystals [5,6], microring resonators [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], and microsphere resonators [26], this new type of sensors can be lighter, more compact and scalable, compared to the bulky conventional ones which are implemented either by free-space optics or by fiber optics. Among the PIC implementations, the sensors based on microring resonators drew particular attention of many researchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent development in photonic integrated circuit (PIC) technologies introduced various new types of sensors [4], including gyroscopes. Utilizing nano-/micro-optical devices such as photonic crystals [5,6], microring resonators [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], and microsphere resonators [26], this new type of sensors can be lighter, more compact and scalable, compared to the bulky conventional ones which are implemented either by free-space optics or by fiber optics. Among the PIC implementations, the sensors based on microring resonators drew particular attention of many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Among the PIC implementations, the sensors based on microring resonators drew particular attention of many researchers. Various configurations have been studied (mostly theoretically) for optical gyroscopes, including coupled resonator optical waveguides (CROW) [7][8][9][10][11][12][13][14][15][16][17], side-coupled integrated spaced sequence of optical resonators (SCISSOR) [18], self-interference add-drop resonators (SIDAR) [19], add-drop multiplexers [20], double-ring resonators [21,22], and Mach-Zehnder interferometer [23]. The main operation principle of the ring-resonator-based optical gyroscopes can be described as the accumulation of the Sagnac phase ( ϕ Sagnac ) while light is rotating around the ring multiple times.…”
Section: Introductionmentioning
confidence: 99%
“…Another multipath resonant structure for gyroscope applications is based on a coupled spiral interferometer that is a spiral waveguide with coupling between adjacent arms [14], having a maximum sensitivity decreasing as the reciprocal of the waveguide loss coefficient. Finally the disorder effects affecting the performance of CROW gyroscopes and largely associated with the fabrication tolerances are discussed in [15,16]. Some potential applications have been identified for the 1D photonic crystal (i.e., Bragg grating) assisted ring resonator, called in this paper the Bragg grating ring resonator (BGRR), such as for add-drop filters and angular velocity sensors [17][18][19][20], but any specific study under rotation conditions has been not yet reported.…”
Section: Introductionmentioning
confidence: 99%
“…Objects that experience moving and/or spinning motion undergo intrinsically distinct scattering signatures [1][2][3][4][5][6][7][8] and require special treatment different from the one of objects at rest [9][10][11][12][13][14][15][16][17][18][19][20]. For example, it was shown in Ref.…”
mentioning
confidence: 99%
“…A simple cylindrical inhomogeneity with finite (of infinite) conductivity is also shown to possess a different scattering response that may be solved by means of the instantaneous rest-frame technique [22,23]. Several promising applications were proposed with spinning building blocks, e.g., waveguide rotation sensor systems [8] or gyroscopes [24,25]. In the same vein, Censor et al analyzed the governing equations of pressure waves (acoustics) [26] in moving or rotating media, and showed that an equivalent wave equation can be derived [27].…”
mentioning
confidence: 99%